Identifying the Purpose Fostering Factors in the Academic Lived Experience of Iranian Male Elites: A Qualitative Study - Mohamadreza Taghizadeh; Mansoureh Haj Hosseini; Elaheh Hejazi Moughari; Keyvan Salehi (پژوهش‌های کاربردی روانشناختی)
The current research endeavored to discern factors leading to the sense of purpose among male elites in school and university. The study implemented a grounded theory research design with the objective of conceptualizing the ordering process, utilizing a constructivist worldview and a qualitative approach. The investigation concentrated on males aged 25 to 45 who were members of the Iranian elite community and resided primarily in Tehran. Data were gathered through 2022 to 2023 through online or in-person semi-structured interviews with sixteen participants who were purposively selected. The Charmaz method was employed to execute analysis and coding in two stages:initial and focused coding, which was facilitated by the MAXQDA 2018 software. In general, three primary themes were identified, along with their respective categories and subcategories: Diversity, effective relationships, and the experience of agency. Effective relationships are defined as the dynamics and individuals that exist within the context of the purposeful individual, including teachers and professors. Taking responsibility in school and university is an example of the experience of agency, which is characterized by self-efficacy and a sense of influence. Experiencing diversity, the final term, denotes an understanding of various scientific and practical disciplines. The results obtained indicate that in order to establish an environment that is conducive to purposefulness, schools and universities must offer contexts that incorporate a variety of scientific, practical, and relational experiences. This will encourage their audience to engage in problem-solving and activation within each domain, thereby enabling students to develop a more autonomous level of self-awareness and contextual understanding, as well as to establish meaningful objectives and actively pursue them.